PEMANFAATAN TANAH LIAT SEBAGAI MEDIA PEMBELAJARAN MOLYMOD BERBASIS GREEN CHEMISTRY PADA MATERI GEOMETRI MOLEKUL SMK KELAS X - Darnisyah Darnisyah; Yulia Safitri; Ira Hidayati (Journal of Chemistry Education and Integration, 2023)
AbstractAbstract Science learning, especially chemistry, also has an important role in shaping the character of a person through the application of scientific properties ranging from investigating, conducting experiments, discussing and communicating experimental results in a scientific process. The Green Chemistry approach is closely related to how to overcome environmental problems. Some studies suggest that green chemistry aims to minimize and or eliminate harmful substances in a chemical process, replaced with substances that are more environmentally friendly so as to overcome environmental problems. The purpose of this study was to determine the use of clay as a green chemistry-based molymod learning medium on molecular geometry material of SMK class X. This research method is descriptive research. This research was conducted in class X TBSM B SMK Negeri 2 North Tambusai which amounted to 19 people. The types of data collection carried out in this study are test and non-test. Test techniques are measurements of learners' abilities. Non-test techniques are carried out through observation of student activities during the learning process. The results showed that the use of clay was more effective in learning molecular geometry than 2D dynamic images. Keywords: Molymod, Green Chemistry, and Molecular Geometry